2018
DOI: 10.3847/1538-4357/aac9b9
|View full text |Cite
|
Sign up to set email alerts
|

The MAVERIC Survey: Still No Evidence for Accreting Intermediate-mass Black Holes in Globular Clusters

Abstract: We present the results of an ultra-deep, comprehensive radio continuum survey for the accretion signatures of intermediate-mass black holes in globular clusters. The sample, imaged with the Karl G. Jansky Very Large Array and the Australia Telescope Compact Array, comprises 50 Galactic globular clusters. No compelling evidence for an intermediate-mass black hole is found in any cluster in our sample. In order to achieve the highest sensitivity to low-level emission, we also present the results of an overall st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
118
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(127 citation statements)
references
References 170 publications
(199 reference statements)
8
118
1
Order By: Relevance
“…Other studies have found no signatures of accretion in large samples, suggesting that the typical masses of IMBHs in globular clusters may be lower than theoretical predictions or the occupation fraciton may be extremely small (e.g. Strader et al 2012;Tremou et al 2018). Using a per BH rate ofṄ BH = 10 −9 yr −1 (see Section 6.1) we can express the volumetric rate asṄ vol ≈ 4 f BH yr −1 Gpc −3 or 0.2 f BH yr −1 Gpc −3 depending on whether or not we include globular clusters associated with dwarf galaxies.…”
Section: Volumetric Event Ratesmentioning
confidence: 92%
“…Other studies have found no signatures of accretion in large samples, suggesting that the typical masses of IMBHs in globular clusters may be lower than theoretical predictions or the occupation fraciton may be extremely small (e.g. Strader et al 2012;Tremou et al 2018). Using a per BH rate ofṄ BH = 10 −9 yr −1 (see Section 6.1) we can express the volumetric rate asṄ vol ≈ 4 f BH yr −1 Gpc −3 or 0.2 f BH yr −1 Gpc −3 depending on whether or not we include globular clusters associated with dwarf galaxies.…”
Section: Volumetric Event Ratesmentioning
confidence: 92%
“…For example, see the studies of: G1, the most massive globular cluster around M31 (Gebhardt et al 2005;Miller-Jones et al 2012); ω Centauri, the most massive globular cluster around the Milky Way (Noyola et al 2008;Haggard et al 2013;Zocchi et al 2017Zocchi et al , 2019; plus other globular clusters around the Milky Way such as M15 (Gebhardt et al 2000;Gerssen et al 2002;Baumgardt et al 2003;Kirsten & Vlemmings 2012;den Brok et al 2014;Kirsten et al 2014); M54 (Ibata et al 2009); 47 Tucanae (Kızıltan et al 2017;Abbate et al 2018;Mann et al 2019);and NGC 6624 (Perera et al 2017;Gieles et al 2018;Baumgardt et al 2019). To date, there remains no conclusive evidence for IMBHs in globular clusters (Hurley 2007;Vesperini & Trenti 2010;Lanzoni & Cosmic-Lab Team 2016;Maccarone 2016;Wrobel et al 2016;Ferraro et al 2018;Tremou et al 2018), although see ). This current status may simply reflect the observational difficulty in detecting low mass black holes in a relatively gas poor environment.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively to an IMBH, the central excess of mass could be explained with a system of stellar dark remnants like massive white dwarfs, neutron stars or black holes. The shaded interval is the allowed IMBH mass range from Tremou et al (2018). We assume a core radius of 0.36 pc as in Baumgardt & Hilker (2018).…”
Section: Resultsmentioning
confidence: 99%
“…(2017). According to searches for accretion signatures (Tremou et al 2018), there is an upper limit on the mass of the IMBH of 1130 M . From the results of our analysis, we cannot either confirm these claims or reduce the upper limits but, using the published optical parameters of M62, we have found that ∼ 4000 M of low luminosity matter must be contained within the central 0.2 pc of the cluster.…”
Section: Discussionmentioning
confidence: 99%